The Role of Universities in Promoting Physical Activities Participation Among Undergraduate Male Students - Sameer Mohammed Sayyd (Jurnal MensSana, 2022)
Engaging in physical activity provides a lot of benefits for the youth. It generally helps to improve fitness. Despite clear evidence that physical activity offers significant health benefits, the majority of youth in Saudi Arabia, do not meet the recommended levels of physical activity as findings show 60 percent of the Saudi Arabian population is physically inactive. This poses a huge problem as sedentary life is a public health issue, lack of policies and funding that will encourage physical activity has been identified as one of the major problems. Therefore, this study examines the role of universities Policy and Funding in promoting physical activities participation among the undergraduates in KSA. Data were collected using questionnaire from 25 universities from the Saudi Kingdom with a total of 643 participants who were selected across all levels. Results show that financial support and policies had high importance in sports participation. Based on these, it can be argued that both university's policies, funding have a positive relationship with physical activities participation.